Екомережа України: ідеологія створення та шляхи формування - ВАКАРЕНКО, ЛЮДМИЛА ПАВЛІВНА; ДУБИНА, ДМИТРО ВАСИЛЬОВИЧ; ШЕЛЯГ-СОСОНКО, ЮРІЙ РОМАНОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Екомережа України: ідеологія створення та шляхи формування